2021
DOI: 10.1007/s10143-021-01598-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and treatment options of radiation-induced brain cavernomas: a systematic review

Abstract: Radiation-induced cavernous malformations (RICMs) are delayed complications of brain irradiation during childhood. Its natural history is largely unknown and its incidence may be underestimated as RCIMS tend to develop several years following radiation. No clear consensus exists regarding the long-term follow-up or treatment. A systematic review of Embase, Cochrane Library, PubMed, Google Scholar, and Web of Science databases, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Ten (1 subacute and 9 late) of these appeared in patients receiving high-dose CSI. The possible development of these vascular changes after radiation for brain tumors and MB in particular is well-documented for photons [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. In a recent study, prevalence of cerebral microbleeds was 90% after a follow-up of 13.5 years in pediatric brain tumor survivors who received radiotherapy [ 52 ], with longer follow-up and higher CSI dose correlating with higher lesion count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten (1 subacute and 9 late) of these appeared in patients receiving high-dose CSI. The possible development of these vascular changes after radiation for brain tumors and MB in particular is well-documented for photons [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. In a recent study, prevalence of cerebral microbleeds was 90% after a follow-up of 13.5 years in pediatric brain tumor survivors who received radiotherapy [ 52 ], with longer follow-up and higher CSI dose correlating with higher lesion count.…”
Section: Discussionmentioning
confidence: 99%
“…Data on their appearance after PT are limited, but they may appear with a shorter latency and are not uncommon [ 55 ]. The best management strategy for these malformations and their natural history is not yet clear: in most cases, they remain asymptomatic and experts believe that a specific treatment should be initiated only for selected symptomatic cases [ 48 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Late complications after intracranial radiotherapy (RT) occur in 1-5% of patients [11,12]. They include delayed cysticercosis, CEH, and cavernous hemangioma; however, the mechanism is not clear [13][14][15][16]. Extracranial RT can cause radiation-induced late bleeding or pseudoaneurysm [4,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of MRI has not only increased the frequency of CM diagnosis, but has also advanced the understanding of natural history and epidemiology [7,[20][21][22][23][24][25]. Because CM is low-pressure and low-flow vascular malformations, single or multiple lumen formations in the vessels are observed on MRI [26].…”
Section: Characteristic Appearances On Magnetic Resonance Imagingmentioning
confidence: 99%
“…The general dose planning method is to exclude the hemosiderin ring and the bleeding site around the lesion because it contains adjacent brain tissue [17,19]. Patet et al [24] reported that radiation-induced cavernosum malformation (RICM) is a delayed complication induced by childhood irradiation. Its natural history is largely unknown and its incidence may be underestimated as RCIMs tend to develop several years following radiation.…”
Section: Gamma Knife Radiosurgerymentioning
confidence: 99%